1999
DOI: 10.1007/s003830050675
|View full text |Cite
|
Sign up to set email alerts
|

Sacrococcygeal teratoma: clinical course and prognosis with a special view to long-term functional results

Abstract: From 1976 to 1995, 23 children, 4 boys and 19 girls, were treated at our department for sacrococcygeal teratomas (SCT). Their records were analyzed retrospectively, considering age at operation, histopathology, recurrences, and long-term evolution. One died on the 1st day of life following tumor rupture with hemorrhagic shock without surgical intervention. All others were operated upon at a mean age of 4.2 days for those 19 (= 82%) who were diagnosed in the neonatal period and whose histology proved benign. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 16 publications
0
33
0
6
Order By: Relevance
“…Four of our patients had malignant histology on presentation; two were lost to follow-up after initial excision and chemotherapy, while two were well at 12 and 24 months after surgical excision and chemotherapy. Even though our patients with malignant disease were few, it would appear that they do well after chemotherapy and excision as noted by Wakhlu et al [8] A number of reports have attempted to assess longterm outcome after treatment of SCT; [8,10,11,[15][16][17] which include continence, quality of life, and sexual function. In one UK study on the long-term followup of children treated for SCT, [18] a third had some functional problems, and Malone et al, found as many as 41% of children treated for SCT with some long-term functional sequelae.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Four of our patients had malignant histology on presentation; two were lost to follow-up after initial excision and chemotherapy, while two were well at 12 and 24 months after surgical excision and chemotherapy. Even though our patients with malignant disease were few, it would appear that they do well after chemotherapy and excision as noted by Wakhlu et al [8] A number of reports have attempted to assess longterm outcome after treatment of SCT; [8,10,11,[15][16][17] which include continence, quality of life, and sexual function. In one UK study on the long-term followup of children treated for SCT, [18] a third had some functional problems, and Malone et al, found as many as 41% of children treated for SCT with some long-term functional sequelae.…”
Section: Discussionmentioning
confidence: 72%
“…Currarino later described three more cases and suggested that the etiology may be related to adhesions between the ectoderm and neural endoderm causing a split notochord. [17] In another report from North-Eastern Nigeria, associated congenital anomalies were noted in three of the patients. [6] In this present report, two children had associated congenital anomalies: one child with congenital heart disease and the other child with anal stenosis with tethering of the cord.…”
Section: Discussionmentioning
confidence: 89%
“…The treatment of choice for SCT is early surgical resection including complete excision of the coccyx. Patients with malignant SCT may be treated with chemotherapy and irradiation in addition to surgical resection [10].…”
Section: Introductionmentioning
confidence: 99%
“…Incomplete excision, incision and drainage of tumour is associated with risk of recurrence and malignant change [8]. The probability of recurrence of tumour is high in the first 2 years after the initial surgery [9]. The recurrence rate is between 3-35% [1,6].…”
Section: Discussionmentioning
confidence: 99%